Observation et modélisation des flux touristiques : application au Mont-Saint-Michel - Cécile Guégan; Cyril Tissot; Sébastien Kervern; David Brosset; Solenn Le Berre; Louis Brigand (Cybergeo, 2015)
The project to restore the maritime setting of the Mont-Saint-Michel and to improve visitor access and experience has led to a major change in how the site can be accessed and visited. To better manage and control tourist flows in a sustainable manner, the local tourism association is in need of decision-making tools. To address this issue, two complementary tools based on observation and modelling approaches were developed. First, an observatory identifies and monitors the main elements of this tourism system. Second, a dynamic model is based on the data generated by the observatory and reveals links among the elements of this system. This site-scale tool, based on multi-agent simulation, was applied to the Mont-Saint-Michel before and after restoration of the visitor access. It simulated visitor itineraries and practices, and it pinpointed areas and periods likely to be problematical for visitors and tourism managers.